Preparation and properties of bismaleimide resins based on novel bismaleimide monomer containing fluorene cardo structure. (March 2016) - Zhang, Liying; Na, Liyan; Xia, Lianlian; Xiong, Xuhai; Fan, Shengdi; Chen, Ping
Novel bismaleimide resins based on 9, 9-bis[4-(4-maleimidophenoxy)phenyl]fluorene (PFBMI), 2, 2′-diallyl bisphenol A (DABPA), and 4, 4′-dimaleimido diphenylmethane (BDM) were prepared in this article. The thermal properties of PFBMI/DABPA in different proportions (1:0.87, 1:1, and 1:1.2) were carefully characterized using differential scanning calorimetry, dynamic mechanical analysis, and thermogravimetric analysis. The results showed that resins had good thermal stabilities especially the one at 1:0.87. Its 10% weight loss reached 433.4°C, and the residual weight percentage (RW%) was more than 50%. In addition, PFBMI was blended into BDM/DABPA in a different ratio, and the curing characteristic, thermomechanical behavior, thermal stability, mechanical properties, and moisture absorption behavior of these blends were investigated. The results revealed that the introduction of PFBMI into BDM/DABPA did not decrease the thermal stability of the modified resins but increased the RW% at 600°C. Moreover, the impact strength of the modified resins can be significantly enhanced; when the ratio is 0.08:1, it increased by 35%. The water absorption rate also decreased with the increase in the concentration of PFBMI. PFBMI monomers play an important role on the toughness reinforcement of the BDM/DABPA resin.